PENGEMBANGAN TES DIAGNOSTIK FOUR TIER MENGGUNAKAN APLIKASI GOOGLE FORM PADA MATERI FLUIDA STATIS SMA PONTIANAK - Prabaningtias, Dea Arsi; Silitonga, Haratua Tiur Maria; Mahmudah, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to produce a four-tier multiple choice objective test on static fluid material to explore the misconceptions of high school students in Pontianak. The method used is Research and Development (R & D) with the Four-D model. The test consists of 20 four-tier multiple choice questions. The trial involved 30 students in a small-scale trial, and 192 students in a large-scale trial. Characteristics used are characteristics of diagnostic tests. Based on data analysis, it was concluded that the diagnostic tests developed can be used to explore misconceptions of students, namely: 1) high content validity 2) validity of valid items, 3) high reliability, 4) moderate level of difficulty, 5) RI according to education level learners. Of these conditions, as many as 20 questions can be used. Keywords: Development Of Four Tier Diagnostic Test, Test Characteristics, Static Fluid.